Nadawanie uprawnień zawodowych w zakresie szacowania nieruchomości - Kłusek, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
In Polish jurisprudence we can distinguish two specific groups of professions: the liberal professions and the professions of public trust. The profession of the real estate appraiser for sure may be ranked as aliberal profession. Nevertheless, there is no certainty if this profession may be ranked as a profession of public trust. Qualification of the real estate appraisers to this second group of professions could be areason to justify achange of the existing regulation concerning empowerment in terms of the real estate evaluation. Therefore there is aneed to determine the legal status of the real estate appraiser profession and to judge the regulations which concern empowerment in terms of real estate evaluation.
Keywords: zawód regulowany i zawód zaufania publicznego; nieruchomości; rzeczoznawca majątkowy; samorząd zawodowy